Cucurbitaceae novae colombianae. – i (1942)
Gurania vaupesana / Gurania polypoda / Gurania brevisepala / Gurania  nervosaz / Gurania macrotricha / Gurania sararensis / Gurania angustiflora / Gurania Castroi / Cayaponia trichocalyx / Cayaponia metensis